ANALYSIS OF COOPERATIVE LAW REFORM IN INDONESIA IN GUARANTEING LEGAL PROTECTION RIGHTS FOR COOPERATIVE - Aryanti, Meryy; Zainal Arifin Hoesein (Ikatan Dosen Menulis, 2025)
Cooperatives as business entities based on the values of togetherness and social justice have a strategic position in the national economic system. However, in practice, many cooperatives face problems, including weak accountability of management, and minimal legal protection for their members. This study aims to examine the direction of cooperative law reform in Indonesia in the context of guaranteeing the rights and legal protection for cooperative members. This study uses a normative legal approach with an analysis of the regulations of the Law and secondary data related to information from the cooperatives that you have. The results of the study indicate that the existing legal instruments have not fully protected the legal position of members as the main subjects in cooperatives. Meanwhile, the central government has currently formed red and white cooperatives in every village throughout Indonesia, which will later present new challenges, especially if not accompanied by adequate legal and institutional supervision. Therefore, regulatory reform is needed that not only strengthens the principles of economic democracy, but also provides a concrete protection mechanism for cooperative members. Reformulation of legal policies must be oriented towards transparency, accountability and member participation in the entire cooperative decision-making process.